2012
DOI: 10.1097/nmc.0b013e31825c99d8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Violence Against Women in Three Communities in Alexandria, Egypt

Abstract: The following recommendations are made: empowering women and girls to lead change by increasing their access to education and information; meeting the needs of abused women; mobilizing advocacy initiative by enlisting social, political, and other leaders to speak about VAW; changing policies and legislation to address gender-based violence; conducting education, awareness, and sensitization programs highlighting the problem; screening for violence in healthcare facilities and developing culture sensitive proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 5 publications
6
17
2
Order By: Relevance
“…These findings are consistent with. [8,14] A growing body of literature, [5,[8][9][10][11]13,15,[19][20][21][22] support our findings that low level of education of the participants was significantly associated with DV. Our results showed that more than two-thirds illiterate ones or those having primary education only reported exposure to DV compared to less than half those having university degree.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…These findings are consistent with. [8,14] A growing body of literature, [5,[8][9][10][11]13,15,[19][20][21][22] support our findings that low level of education of the participants was significantly associated with DV. Our results showed that more than two-thirds illiterate ones or those having primary education only reported exposure to DV compared to less than half those having university degree.…”
Section: Discussionsupporting
confidence: 80%
“…In agreement with, [8,10,13,14] DV was found to be significantly associated with working status of the women, additionally, results of univariate logistic regression analysis showed that risk of DV was 2.8 times higher among homemakers than working women. This is because financial independency of the woman is supposed to be protective against DV, moreover, these women who were dependent on their husband for their basic demands, usually accept and tolerate the violence committed against them.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…However, none of these studies identified the factors associated with DV, which is an important step towards designing effective DV prevention programmes. This study was designed to identify the factors, such as the woman's educational status,9 10 occupation,9 11 age,10 12 13 socioeconomic status,9 14 alcohol consumption10–14 and number of children,11 15 which have been reported to be significantly associated with spousal abuse.…”
Section: Introductionmentioning
confidence: 99%